Promoter-Guided Reaction Intermediate Dynamics Enhance Perhydro-benzyltoluene Dehydrogenation - On, Eui-Rim; Lee, Kimoon; Kwak, Yeonsu; Kim, Chan; Dao, Quan; Sohn, Hyuntae; Nam, Suk Woo; Kim, Joohoon; Kim, Yongmin; Jeong, Hyangsoo (American Chemical Society, 2025)
The dehydrogenation of perhydrobenzyltoluene (H-12-BT) as a liquid organic hydrogen carrier presents significant challenges in reaction kinetics and catalyst stability. The reaction pathway involves multiple intermediates and isomeric variations, creating an intricate network that influences both catalytic activity and deactivation mechanisms. While sulfur modification of Pt/theta-Al2O3 catalysts enhances reaction rates and stability, the underlying mechanisms governing catalyst-intermediate interactions have remained elusive. To unravel these complex interactions, we developed a surrogate approach using single-ring model compounds (methylcyclohexane, dimethylcyclohexane, toluene, and xylene) as surrogates for two-ring intermediates. This strategy enabled systematic analysis of intermediate behavior without requiring challenging intermediate synthesis. Using in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) at 320 degrees C, we examined how sulfur modification transforms reaction pathways and surface chemistry. Our results reveal that successful dehydrogenation depends on controlled intermediate readsorption patterns. Sulfur modification promotes favorable readsorption via aliphatic moieties, facilitating complete dehydrogenation while minimizing aromatic species retention. In contrast, unmodified Pt/theta-Al2O3 exhibits preferential readsorption of dehydrogenated aromatic species, leading to active-site blockage and carbon formation. Postreaction analyses confirm that sulfur maintains catalyst integrity by redirecting reaction pathways, demonstrating a broader strategy for controlling surface chemistry in complex dehydrogenation systems through selective adsorption modification.